2016
DOI: 10.1021/acschembio.6b00147
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Recognition and Tools to Study Modulation of r(CGG)exp in Fragile X-Associated Tremor Ataxia Syndrome

Abstract: RNA transcripts containing expanded nucleotide repeats cause many incurable diseases via various mechanisms. One such disorder, fragile X-associated tremor ataxia syndrome (FXTAS), is caused by a noncoding r(CGG) repeat expansion (r(CGG)exp) that (i) sequesters proteins involved in RNA metabolism in nuclear foci, causing dysregulation of alternative pre-mRNA splicing, and (ii) undergoes repeat associated non-ATG translation (RANT), which produces toxic homopolymeric proteins without using a start codon. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Other viral RNAs such as the hepatitis C virus internal ribosomal entry site (HCV IRES) and Influenza A have been focus of several targeting studies (Dibrov, et al, 2014; Lee, et al, 2014). Recently, several small molecules have been designed to target nucleotide repeat expansions including fragile X-associated tremor ataxia syndrome (FXTAS; CGG) (Yang, et al, 2016), myotonic dystrophy type 1 (DM1; CUG) (Gareiss, et al, 2008; Jahromi, et al, 2013; Pushechnikov, et al, 2009), myotonic dystrophy type 2 (DM2; CCUG) (Childs-Disney, et al, 2014), Huntington’s disease (HD; CAG) (Kumar, et al, 2012), and frontotemporal dementia and amyotrophic lateral sclerosis (c9FTD/ALD; G 4 C 2 ) (Su, et al, 2014). A salient question is if small molecules that target non-coding RNAs can be identified and developed into medicines or chemical probes.…”
Section: Introductionmentioning
confidence: 99%
“…Other viral RNAs such as the hepatitis C virus internal ribosomal entry site (HCV IRES) and Influenza A have been focus of several targeting studies (Dibrov, et al, 2014; Lee, et al, 2014). Recently, several small molecules have been designed to target nucleotide repeat expansions including fragile X-associated tremor ataxia syndrome (FXTAS; CGG) (Yang, et al, 2016), myotonic dystrophy type 1 (DM1; CUG) (Gareiss, et al, 2008; Jahromi, et al, 2013; Pushechnikov, et al, 2009), myotonic dystrophy type 2 (DM2; CCUG) (Childs-Disney, et al, 2014), Huntington’s disease (HD; CAG) (Kumar, et al, 2012), and frontotemporal dementia and amyotrophic lateral sclerosis (c9FTD/ALD; G 4 C 2 ) (Su, et al, 2014). A salient question is if small molecules that target non-coding RNAs can be identified and developed into medicines or chemical probes.…”
Section: Introductionmentioning
confidence: 99%
“…CGG repeats also produces toxic polyglycine protein, FMRpolyG via repeat-associated non-AUG (RAN) translation (Todd et al, 2013;Sellier et al, 2017). Previous studies have shown that selective targeting of CGG hairpin structures via small molecules to reduce both RNA foci and PolyG aggregates formation is the most successful approach (Yang et al, 2015(Yang et al, , 2016b. Thus, we sought to find out natural small molecule FIGURE 6 | In vitro potency of Curcumin in FXTAS cultured cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the identification of small molecules targeting expanded CGG RNA repeats [r(CGG) exp ] causing FXTAS. Ideally, a potential compound would prevent non-canonical translation of the CGG repeats sequence into the toxic FMRpolyG protein, as well as correct the alternative splicing defects caused by sequestration of RNA regulatory proteins by expanded CGG nucleotide (Yang et al, 2015(Yang et al, , 2016bVerma et al, 2019b). Here, we found that Curcumin, a polyphenol used as a traditional herbal medicine, binds to CGG RNA repeats (Nafisi et al, 2009;Kulkarni and Dhir, 2010).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations